Dyes and Pigments Novel Applications and Waste Treatment - Papadakis, Raffaello (IntechOpen, 2021)
Dyes and pigments have been utilized since ancient times. They play an important role in everyday life and their use is interwoven with human culture. Even though numerous dyes and pigments have been synthesized to date, and a lot of knowledge has been gained regarding their production and properties, scientific research is pushing the boundaries towards novel dyes and pigments for high-tech applications. At the same time, the accumulation of dyes and pigments in natural environments and pollution of water resources due to their massive use are important consequences to consider. New methods for the degradation and removal of dyes and pigments from affected areas are highly sought after. As such, this book examines new trends in smart and functional dyes and pigments and their uses as well as novel treatment approaches to dye and pigment waste.